PKB signaling and atrogene expression in skeletal muscle of aged mice - Gaugler, Megan (American Physiological Society, 2011)
The purpose of this study was to determine if PKB signaling is decreased and contractile protein degradation is increased in extensor digitorum longus (EDL) and soleus (SOL) muscles from middle-aged (MA) and aged (AG) mice. We also examined the effect of age on atrogene expression in quadriceps muscle. PKB activity, as assessed by Thr(308) and Ser(473) phosphorylation, was significantly higher in EDL and SOL muscles from AG than MA mice. The age-related increase in PKB activity appears to be due to an increase in expression of the kinase, as PKB-α and PKB-β levels were significantly higher in EDL and SOL muscles from AG than MA mice. The phosphorylation of forkhead box 3a (FOXO3a) on Thr(32), a PKB target, was significantly higher in EDL muscles from AG than MA mice. The rate of contractile protein degradation was similar in EDL and SOL muscles from AG and MA mice. Atrogin-1 and muscle-specific RING finger protein 1 (MuRF-1) mRNA levels did not change in muscles from AG compared with MA mice, indicating that ubiquitin-proteasome proteolysis does not contribute to sarcopenia. A significant decrease in Bcl-2 and 19-kDa interacting protein 3 (Bnip3) and GABA receptor-associated protein 1 (Gabarap1) mRNA was observed in muscles from AG compared with MA mice, which may contribute to age-related contractile dysfunction. In conclusion, the mechanisms responsible for sarcopenia are distinct from experimental models of atrophy and do not involve atrogin-1 and MuRF-1 or enhanced proteolysis. Finally, a decline in autophagy-related gene expression may provide a novel mechanism for impaired contractile function and muscle metabolism with advancing age.